2016
DOI: 10.1037/pha0000092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on sensitivity to reinforcement delay and to reinforcement amount in pigeons: Implications for impulsive choice.

Abstract: Methylphenidate has been shown to decrease impulsive choice (increase choices of a larger more delayed reinforcer). The purpose of this study was to investigate 2 potential behavioral mechanisms of this effect: a drug-induced change in control by reinforcement delay (Experiment 1) and/or by reinforcement amount (Experiment 2). In Experiment 1, pigeons responded under a rapid-acquisition, concurrent-chains choice procedure involving delay to reinforcement; the option with the shorter delay varied unpredictably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
1
13
2
Order By: Relevance
“…Ta et al (2008) found that amphetamine decreases sensitivity to delayed reinforcement, and Maguire et al (2009) observed decreases in sensitivity to reinforcement amount following amphetamine administration. However, although methylphenidate selectively decreased sensitivity to probabilistic reinforcement in the current experiment, Pitts et al (2016) found that methylphenidate decreases sensitivity to delayed reinforcement and sensitivity to reinforcer amount. This discrepancy may due to the species used across experiments (rat in the current experiment; pigeon in Pitts et al, 2016) or may be due to procedural differences.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Ta et al (2008) found that amphetamine decreases sensitivity to delayed reinforcement, and Maguire et al (2009) observed decreases in sensitivity to reinforcement amount following amphetamine administration. However, although methylphenidate selectively decreased sensitivity to probabilistic reinforcement in the current experiment, Pitts et al (2016) found that methylphenidate decreases sensitivity to delayed reinforcement and sensitivity to reinforcer amount. This discrepancy may due to the species used across experiments (rat in the current experiment; pigeon in Pitts et al, 2016) or may be due to procedural differences.…”
Section: Discussioncontrasting
confidence: 84%
“…Primarily, these studies have tested psychostimulant drug effects on choice controlled by several dimensions of reinforcement, such as delayed reinforcement and reinforcement magnitude. The drugs d -amphetamine and methylphenidate decrease sensitivity to reinforcement delay (Pitts et al, 2016; Ta et al, 2008) and reinforcement amount (Maguire et al, 2009; Pitts et al, 2016). While dependent schedules have been used to assess the neurochemical basis of delayed reinforcement (i.e., impulsive choice), they have not been used to study the neurochemical basis of probability discounting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if a drug alters sensitivity to reinforcer magnitude, control experiments can be conducted in which subjects respond for reinforcers that differ in magnitude only. For example, Pitts, Cummings, Cummings, Woodcock, and Hughes (2016) tested the effects of methylphenidate on sensitivity to delayed reinforcement and sensitivity to reinforcer magnitude by conducting two experiments. In Experiment 1, the delay to reinforcement differed across two reinforcer alternatives but magnitude was held constant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar functions have been observed across a wide variety of animal species (Addessi, Paglieri, & Focaroli, 2011; Dandy & Gatch, 2009; Green, Myerson, & Calvert, 2010; Stevens, Hallinan, & Hauser, 2005; see review by Vanderveldt, Oliveira, & Green, 2016). Other work has further isolated the role of delay in intertemporal choices by evaluating other behavioral mechanisms involved, such as magnitude discriminations (e.g., Pitts, Cummings, Cummings, Woodcock, & Hughes, 2016; Pitts & Febbo, 2004; Strickland, Feinstein, Lacy, & Smith, 2016) and probability (e.g., Green & Myerson, 2004).…”
Section: On Intervening Variables and Hypothetical Constructsmentioning
confidence: 99%